The impact of green logistics-based activities on the sustainable monetary expansion indicators of Oman - Faris Nasif Al-Shubiri (Journal of Industrial Engineering and Management (JIEM), 2017)
Purpose: The purpose of this study is to examine green logistic activities by three axes (financial economic, social and environment activities) and how these activities affect on sustainable monetary expansion indicators as an evidence of Sultanate of Oman. Design/methodology/approach: This study began by definition elements of logistic green and how evolution of this concept in recent years. This concept analyzed after survey of previous studies on green logistic. The independent variables of green logistic are includes of three components of financial economic, social and environment and applies these components to clarify the impact on expansionary monetary policy indicators ( broad, narrow and reserve money ) as a important signals in determining a country's economy. This study used data published in statistical annual report of central bank of Oman as representative of country economic of sultanate of Oman from the period 2008 to 2015. Findings: The results found two variables of government support to electricity sector (GSE) and subsidy on soft loans to private sector and housing (SSLPH) based on environment activities are statistical significant 1% and 5%. Only one variable of transport and communication (TC) in financial economic activates is statistical significant at 1% and 5% , but all variables community, social and personal (CSP) , cultural and religious affairs (CRA) and social security and welfare (SSW) in social activities are statistical significant at 1% 5% and 10% , finally , also the multiple regression test run of all variables of green logistics activities and each monetary expansion indicators and found there are a statistical significant at 1% and 5%, .The study recommends that should be attention with financial economic activities as a quantitative standard contributes to build the green logistic by diagnosed the priorities and existing economic and financial system that contributes of sustainable development system in the country's economy also activating the industrial sectors by reducing operating costs and improving the quality of service provided to customers as an indicator of social activities to building green logistic and increase corporate awareness about an environmental variables and behavior of consumers to establish financial and economic system based on green logistical concept. Research limitations The available data in statistical annual report of Oman is limited, which limited of the period and all variables of the study. Practical implications: The management of firms should be adopting of green logistic operations by comparing the results of these concepts with competitors in the market for concentrated position of these firms in the market. Also this concept of green logistic helps firms to build an intellectual model that's contributes to enhance the value-added. The results of this study enhance the stability of monastery policy indicators that's reflecting of growth economic. Social implications: Green logistic is presenting a behavior role on the firm's and country performance and determines the trends and attitudes of future growth of firms especially in environment indicator. Originality/value: This study aims to analysis the green logistic in the financial economic, social and environment that's reflect more variations especially as they affected by changes of global markets, particularly with respect to the oil price, which is the main source of revenue for the Sultanate of Oman as the green logistic is one of the modern concepts is influencing the construction of corporate strategies to build economic plans of the country. Also this study has supplied researcher's conceptual framework to explain the green logistic in preparation for many future studies to examine the elements of green logistic.
Keywords: 650; green logistic activities; monetary expansion; sustainable development; sultanate of Oman